Absolute and Relative Activity of Microencapsulated Natural Essential Oils against the Larvae of Carpet Beetle Anthrenus flavipies (LeConte). (11th November 2014) - Udakhe, Jayant; Shrivastava, Neeraj; Honade, Smita; Banait, Dhanashree; Sonawane, Namita
Abstract : This study focuses on finding natural ecofriendly alternatives to the existing commercial Anthrenus flavipies resist chemicals. Eucalyptus, lavender, and citronella microcapsules were explored as natural alternatives. Chemical contents of microcapsules and fragrance releasing property were tested using gas chromatography. Absolute (proofing) and relative (repellent) activities of microcapsule treated fabrics were tested against the larvae of carpet beetle Anthrenus flavipies (LeConte). Proofing activity test results revealed that natural essential oils act as a deterrent for Anthrenus flavipies, but give lesser protection compared to commercial chemical permethrin. Repellency test results also affirmed these findings and it was observed that Anthrenus flavipies prefers to eat untreated fabric compared to its treated counterpart.